Gendering the Decision-Making Positions in Higher Education: A Cross-Sectional Gender Audit in Three Selected Universities in Malawi - Juliet Chiwaya Kamwendo (African Journal of Inter-Multidisciplinary Studies)
Malawi is one of the countries that has doubled its efforts to narrow the gender gap since the 1995 Beijing Platform for Action. The country ratified both international and regional gender protocols as well as enacting the national gender policy to safeguard gender equality at all levels to empower women. The participation of women in decision-making positions is therefore critical at this point. Many researchers globally have claimed that having more women in strategic leadership roles would help to reduce workplace restrictions and influence policies. This paper therefore discusses the gender representation of women in decision-making in higher education at University of Malawi, the Malawi University of Science and Technology, and Mzuzu University. The findings reveal a stagnated culture of colonial regime sustained by with patriarchal structure which continue to favour men in decision-making positions at the expense of women. In addition, all three institutions suffer gender-blind promotion criteria and systematic institutional resistance which makes it difficult for women to ascend to decision-making positions hence the hierarchy is highly dominated by males. The paper provides recommendations as follows: (i) promoting women in research in order to allow more women in positions of decision-making, (ii) repurposing the institution gender policies, (iii) women agency change of mindset and make concerted efforts to emancipate themselves from negative stereotypes and barriers in institutions.